Pengaruh Likuiditas, Solvabilitas, dan Profitabilitas terhadap Nilai Perusahaan (Studi Kasus pada Perusahaan LQ 45 Periode 2013-2022) - Nani Hartati; Miftakul Huda; Nur Hidayati (Apik Cahaya Ilmu, 2026)
This study aims to analyze the effect of liquidity, solvability, and profitability on firm value in companies listed in the LQ 45 index on the Indonesia Stock Exchange (IDX) for the period 2013-2022. The study employs a quantitative approach using secondary data from annual financial reports. The population consists of 45 LQ 45 companies, and through purposive sampling, 14 companies were selected as samples over 10 years, resulting in 140 observations. The independent variables include liquidity proxied by the Current Ratio (CR), solvability proxied by the Debt to Equity Ratio (DER), and profitability proxied by Return on Assets (ROA). The dependent variable is firm value proxied by Price Earning Ratio (PER). Data analysis uses panel data regression with Eviews. Model selection through the Chow Test and Hausman Test yields the Fixed Effect Model (FEM). The results indicate that liquidity (CR) has a positive and significant effect on firm value, solvability (DER) has a negative and insignificant effect on firm value, while profitability (ROA) has a positive and significant effect on firm value. The adjusted R² of 0.771 indicates the three variables explain 77.1% of the variation in firm value.